Synthesised fractional-order PD controller design for fractional-order time-delay systems based on improved robust stability surface analysis - Zhang, Shuo; Liu, Lu; Chen, Yang Quan; Xue, Dingyu (IET control theory & applications, 2020)
An improved robust stability surface analysis method is proposed in this study for fractional-order time-delay systems. Through the stabilisation process, a synthesised fractional-order PD controller can be designed with guaranteed robustness specifications. Firstly, the specification for improved robustness requirements is proposed. In order to find selectable robust controller design parameter combinations for the controlled system, stability region is discussed based on the stability boundary locus, and the robust stability surface is derived straight after. Secondly, the selectable parameter combinations are checked to find the one that best fulfils all the proposed robustness specifications. Finally, numerical simulations are given to demonstrate the effectiveness and flexibility of the presented control algorithm.